The clerodane diterpene casearin J induces apoptosis of T-ALL cells through SERCA inhibition, oxidative stress, and interference with Notch1 signaling - De Ford, Christian (2016)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic malignancy that preferentially affects children and adolescents. Over 50% of human T-ALLs possess activating mutations of Notch1. The clerodane diterpene casearin J (CJ) is a natural product that inhibits the sarcoendoplasmatic reticulum calcium ATPase (SERCA) pump and induces cell death in leukemia cells, but the molecular mechanism of cytotoxicity remains poorly understood. Here we show that owing to SERCA pump inhibition, CJ induces depletion of the endoplasmic reticulum calcium pools, oxidative stress, and apoptosis via the intrinsic signaling pathway. Moreover, Notch1 signaling is reduced in T-ALL cells with auto-activating mutations in the HD-domain of Notch1, but not in cells that do not depend on Notch1 signaling. CJ also provoked a slight activation of NF-κB, and consistent with this notion a combined treatment of CJ and the NF-κB inhibitor parthenolide (Pt) led to a remarkable synergistic cell death in T-ALL cells. Altogether, our data support the concept that inhibition of the SERCA pump may be a novel strategy for the treatment of T-ALL with HD-domain-mutant Notch1 receptors and that additional treatment with the NF-κB inhibitor parthenolide may have further therapeutic benefits.